The Impact of War on the Global Economy: Challenges and Opportunities for the Indonesian Defense Industry - Ramadhoni, M. Bram Efano; Siahaan, Timbul; Khaerudin; Jandhan, I.B Putra (Jurnal Multidisiplin Madani, 2024)
War exerts a substantial influence on the economy, affecting the levels of production, consumption, and international trade. The defense industry is essential to a country's economic framework, especially in addressing global shifts. The objective of this research is to evaluate the influence of war on worldwide economic stability, analyze how the Indonesian defense sector tackles global issues, and provide measures to improve market share. The research will utilize qualitative approaches, including descriptive case studies. In order to strengthen the domestic defense sector, it is necessary to enact policies that enhance infrastructure, human resources, budgetary assistance and promote both national and international strategic collaboration. To achieve self-sufficiency in supplying defense equipment, minimize dependence on imports, and support Indonesia's goal of becoming a global maritime power, it is crucial to prioritize research and development, technology transfer, and the improvement of defense industry facilities and infrastructure. Enhancing the national military industry not only functions as a defensive strategy but also boosts economic competitiveness. Pursuing autonomous development of the industry will make a significant contribution to the economy, foster job creation, and uphold national security. The commitment and cooperation of the government, industry, and relevant institutions are crucial for achieving Indonesia's aim of becoming an independent and globally competitive military force